Power Relations in Gender-Based Violence From the Criminological Aspect - Samantha Varania Ekasuci; Hana Faridah (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2022)
Gender-based violence is more commonly assumed with women and girls than with men. Gender-based violence exists because of inequality in power relations and patriarchal culture embedded in society. Power can make a person feel entitled to act arbitrarily against others who are considered inferior. Behavior based on this kind of thinking allows a person to be violent towards others. Furthermore, this paper explains various theories of the crime of sexual violence when examined from a criminological perspective. The research method used in this paper is normative juridical through a case-based approach and legal system. The sources used include primary legal materials, secondary legal materials and tertiary legal materials.